Nutrients deficiencies in patients with autism spectrum disorder, role of folic acid and vitamin D3 - review of literature - Małachowska, Dominika; Świercz, Aleksandra; Żurek, Urszula; Tołwiński, Ignacy; Kędzierska, Zofia; Antkowiak, Klaudia; Dadas, Klaudia; Ciecierski-Koźlarek, Hubert; Shved, Kateryna (Journal of Education, Health and Sport, 2023)
Introduction and purpose: This article will discuss the relationship between nutrition deficiency, focusing on folic acid and vitamin D3 and autism spectrum disorder (ASD). Research suggests that nutrient deficiencies play a role in the development and progression of autism. This article will investigate causes of nutrient deficiencies in ASD, like dietary constraints, food choice, and environment exposure, and their impact on ASD and related symptoms. The purpose of this article is to provide an overview of the research examining the relationship between folic acid and vitamin d3 supplementation and autism. Materials and methods: A broad search was conducted using the PubMed database in order to identify relevant studies published between 2010-2020 using keywords such as “folic acid”, “folinic acid”, "vitamin d3", "autism spectrum disorder". A brief description of the current state of knowledge: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder that in recent years has been increasingly diagnosed among children. Only between 2016 and 2014 measured prevalence in the United States has increased by 10%. [1] The exact etiology of ASD in not known. In this review we will examine a role of folic acid and vitamin D3. Research suggests that folic acid supplements can help improve verbal skills in people with ASD. Research also shows decreased levels of vitamin d3 in ASD patients. Clinical trials involving vitamin d3 present inconclusive data but lean towards positive impact of supplementation. Both folic acid and vitamin d3 supplementation is safe. Dietary changes and oral supplementation may be beneficial for patients. Conclusions: Studies with larger participant numbers should be done to prove the significance of folic acid and vitamin D3 supplementation as it shows potential in being a safe and not expensive complementary therapeutic option.